Predicting Maximal Dynamic Strength From the Load-Velocity Relationship in Squat Exercise. Issue 7 (July 2015) - Bazuelo-Ruiz, Bruno; Padial, Paulino; García-Ramos, Amador; Morales-Artacho, Antonio J.; Miranda, María T.; Feriche, Belén
Abstract : Abstract: Bazuelo-Ruiz, B, Padial, P, García-Ramos, A, Morales-Artacho, AJ, Miranda, MT, and Feriche, B. Predicting maximal dynamic strength from the load-velocity relationship in squat exercise. J Strength Cond Res 29(7): 1999–2005, 2015—The aim of this study was to develop a rapid indirect method to determine an individual's maximal strength or 1 repetition maximum (RM) in untrained subjects during half-squat exercise. One hundred and five physically active young subjects (87 men and 18 women) performed a submaximal and a maximal load test during half-squat exercises on a Smith machine. In the submaximal test, subjects completed 3 repetitions with a load equivalent to body weight. The velocity and power of barbell displacement were recorded during the upward movement from 90° of knee flexion. All repetitions were performed at maximum velocity. In a subsequent 1–2RM test, the 1RM for the exercise was calculated. The variables' load and mean velocity (Vmean ) were used to construct an adjusted 1RM prediction model, which was capable of estimating the 1RM with an accuracy of 58% ( F exp = 72.82; 2; 102 df ; p ⩽ 0.001). Our results indicate a good correlation between the mean displacement velocity of a load equivalent to body weight and 1RM. This relationship enables a safe and fast estimation of 1RM values in half-squat exercise (1RM = −61.93 + [121.92·Vmean ] + [1.74·load]) and provides valuable information to untrained subjects who are starting resistance training programs.